UPAYA MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS 9B MATERI ADVERTISEMENT TEXT MENGGUNAKAN MEDIA BOARD GAME DENGAN METODE BLENDED LEARNING - Endarwati, Endarwati (CV Sintesia, 2024)
This research aims to find out the increasing activeness of students learning in online learning through the media board games in English subjects. This study is a class action study with the research subjects of grade IX students MTs N 2 Mojokerto as many as 30 people. This research was conducted 2 cycles, each cycle consisting of 2 meetings. At each meeting consists of 4 stages namely planning, implementation, observation and reflection. Data collection techniques used include interviews and observations. Based on the results of the study, in cycle I obtained an average student learning activity of 65.63% with enough categories. while in cycle II, the average learning activity of students is 79.69% with a high category. Thus, from cycle I and cycle II there was a 14.06% increase in student activity. thus it can be concluded that through the board games can increase the active learning of grade IX students of MTs N 2 Mojokerto towards English speaking skills, especially advertisement text materials in online learning during the covid-19 pandemic.